The relationship of gymnastics experience and hand placement technique on peak ground reaction forces through the elbow - Richter, S.; Bolte, J. H.; Boucher, L. C. (The Journal of Sports Medicine and Allied Health Sciences, 2017)
Gymnastics has a lifetime cumulative injury rate of 58%, with 13-53% of injuries occurring at the upper limb.1-3 Back handsprings (BHS) are a common skill used in gymnastics.3 BHS and similar upper limb loading skills may occur over 100 times per practice.4 Current literature states, a turnedin hand position reduces peak ground reaction force at impact on floor, thus reducing the risk of injury.5,6 To our knowledge no studies analyzing the role of gymnastics experience and hand placement during a BHS on the balance beam (BB) exist. OBJECTIVE The purpose of this study was to identify how gymnastics experience and hand placement during a BHS on BB affects peak ground reaction forces.